1990
DOI: 10.1182/blood.v76.8.1647.bloodjournal7681647
|View full text |Cite
|
Sign up to set email alerts
|

B-cell differentiation following autologous, conventional, or T-cell depleted bone marrow transplantation: a recapitulation of normal B-cell ontogeny

Abstract: The circulating lymphocytes of 88 consecutive patients following autologous, conventional, or T-cell depleted bone marrow transplantation were serially analyzed for B-cell surface antigen expression and function. In the majority of patients, except for those who developed chronic graft-versus-host disease, the number of circulating CD20+ B cell normalized by the fourth posttransplant month. The earliest detectable B cells normally expressed HLA-DR, CD19, surface immunoglobulin (slg), CD21, Leu-8, and lacked ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1
4

Year Published

1993
1993
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 0 publications
5
25
1
4
Order By: Relevance
“…1). For all groups, we observed supranormal absolute B‐cell numbers throughout the year post‐transplantation, as described earlier in clinical studies [19, 20]. There were no statistical significant differences in the reconstitution pattern between the groups after transplantation.…”
Section: Resultssupporting
confidence: 85%
“…1). For all groups, we observed supranormal absolute B‐cell numbers throughout the year post‐transplantation, as described earlier in clinical studies [19, 20]. There were no statistical significant differences in the reconstitution pattern between the groups after transplantation.…”
Section: Resultssupporting
confidence: 85%
“…It was previously reported that NOD/SCID mice engrafted with human cord‐blood‐derived HSC generate high levels of CD19 + CD5 + human B lymphocytes in the lymphoid tissues 14 . It is possible that the fetal progenitor cells (cord blood or fetal‐liver‐derived HSC) in comparison with their adult counterpart (mobilized peripheral blood or bone‐marrow‐derived HSC) has a higher potential to differentiate into CD5 + B cells; however, it has also been demonstrated that the lack of optimal T‐cell–B‐cell signalling may bias the B‐cell developmental pathway towards the production of this B‐cell subset 34 . As implantation of human fetal thymus in the BLT model resulted in apparently normal T‐cell development (determined by surface marker expression, see supplementary material, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Small et al (1990), 25 o número relativo e absoluto de células circulantes expressando CD19 e CD20, dois marcadores das células B maduras, aparece diminuído durante os três primeiros meses após o transplante. Além disso, durante o primeiro ano pós-transplante, a maioria das células B expressa marcadores de fenótipos indiferenciados, como CD23 e CD38.…”
Section: Reconstituição Da Resposta Humoralunclassified